Acesso do trabalhador ao programa saúde da família: estudo de caso em uma unidade básica de saúde de Mossoró-RN - Freitas, Kalidyjamayra Oliveira Reis de (Universidade Federal Rural do Semi-Árido, 2017)
The Health of the worker must, as per the regulations of the Unified Health System, be contemplated in the actions and services provided by the Family Health Program, as primary health care, in order to guarantee the worker's access in a comprehensive, universal and equitable way with a Looking at Occupational Health Surveillance from the perception of the SUS user as a worker inserted in the process of production and social reproduction. This study is a qualitative research with the objective of analyzing the worker's access to the FHP, specifically in relation to Surveillance in Worker's Health, in the perception of health professionals. Semi-structured interviews were conducted with professionals according to the category, except the physician, who make up the PSF team of a basic health unit in the periphery of the municipality of Mossoró / RN in May 2017. Based on data analysis, it was identified that no There is a guarantee of the user's access, as a worker, to the FHP because he can not perceive it in his practice of care, and thus, there are no actions aimed at Occupational Health Surveillance or intervention capable of changing the reality of risks and diseases that affect About the worker in his or her work space. It is challenging for managers, healthcare professionals, users and organized civil society to think and act with the understanding that every user, regardless of the reason or motive that made him seek the service, should be seen as an active worker, and even inactive, considering Their mode of production and social insertion as a determining factor of their health-disease process.
Monografia
Keywords: Trabalhador; Programa Saúde da Família; Acesso; Vigilância; Worker; Family Health Program; Access; Surveillance; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO